Clinical Geriatric Psychopharmacology. - Salzman, Carl (Wolters Kluwer Health, 2011)
Thoroughly updated for its Fourth Edition, this volume is the most authoritative clinical reference on the pharmacologic treatment of psychiatric disorders in elderly patients. This edition provides complete information on new psychotropic drugs, new uses for established drugs, and clinically relevant advances in the neurosciences. Four new chapters cover genes, pharmacokinetics, and their impact on prescribing; new cognitive-enhancing strategies and drugs; late-life depression and physical illness; and depression and cardiac disease in late life. The book offers detailed guidelines-including.